Identification of loss-of-function mutations of SLC35D1 in patients with Schneckenbecken dysplasia, but not with other severe spondylodysplastic dysplasias group diseases. Issue 8 (8th June 2009) - Furuichi, T; Kayserili, H; Hiraoka, S; Nishimura, G; Ohashi, H; Alanay, Y; Lerena, J C; Aslanger, A D; Koseki, H; Cohn, D H; Superti-Furga, A; Unger, S; et al.
Abstract : Background: Schneckenbecken dysplasia (SBD) is an autosomal recessive lethal skeletal dysplasia that is classified into the severe spondylodysplastic dysplasias (SSDD) group in the international nosology for skeletal dysplasias. The radiological hallmark of SBD is the snail-like configuration of the hypoplastic iliac bone. SLC35D1 (solute carrier-35D1) is a nucleotide-sugar transporter involved in proteoglycan synthesis. Recently, based on human and mouse genetic studies, we showed that loss-of-function mutations of the SLC35D1 gene ( SLC35D1 ) cause SBD. Object: To explore further the range of SLC35D1 mutations in SBD and elucidate whether SLC35D1 mutations cause other skeletal dysplasias that belong to the SSDD group. Methods and results: We searched for SLC35D1 mutations in five families with SBD and 15 patients with other SSDD group diseases, including achodrogenesis type 1A, spondylometaphyseal dysplasia Sedaghatian type and fibrochondrogenesis. We identified four novel mutations, c.319C>T (p.R107X), IVS4+3A>G, a 4959-bp deletion causing the removal of exon 7 (p.R178fsX15), and c.193A>C (p. T65P), in three SBD families. Exon trapping assay showed IVS4+3A>G caused skipping of exon 4 and a frameshift (p.L109fsX18). Yeast complementation assay showed the T65P mutant protein lost the transporter activity of nucleotide sugars. Therefore, all these mutations result in loss of function. No SLC35D1 mutations were identified in all patients with other SSDD group diseases. Conclusion: Our findings suggest that SLC35D1 loss-of-function mutations result consistently in SBD and are exclusive to SBD.